Towards Achieving Electronic Human Resource Management: Challenges Facing Public Enterprises in Adopting Technology - Arvid Muzanenhamo; Sabina Duduzile Khazamula; Mathias Imbayarwo (CV. Literasi Indonesia, 2023)
This study examined the challenges that are faced by South African public enterprises in implementing digitalization in the Human Resource Management (HRM) department. A qualitative research approach was used with data obtained using structured interviews from a public enterprise, and Human Resource Practitioners were used to conduct interviews in this study. Purposive non-probability sampling was applied in engaging 15 participants in a public corporation and data was analyzed using thematic analysis. The study revealed that HRM departments do not entirely make use of technology in their operations. The inability to use technology is due to a lack of in-house digital training, and the organization’s inability to quickly swiftly respond to environmental changes due to bureaucratic structure. It was therefore recommended that public entities embark on extensive employee digital training and implementation of effective internal digital systems for organizational effectiveness.